Influence of Pd-loading on gas sensing characteristics of SnO2 thick films - Bagal, L. K.; Patil, J. Y.; Mulla, Imtiaz S.; Suryavanshi, S. S. (Ceramics International, 2012)
Nanocrystalline pristine and 0.5, 1.5 and 3.0 wt% Pd loaded SnO2 were synthesized by a facile co-precipitation route. These powders were screen-printed on alumina substrates to form thick films to investigate their gas sensing properties. The crystal structure and morphology of different samples were characterized by using X-ray diffraction, scanning electron microscopy and transmission electron microscopy techniques. The 3.0 wt% Pd:SnO2 showed response of 85% toward 100 ppm of LPG at operating temperature of 250 degrees C with fast response (8 s) and quick recovery time (24 s). The high response toward LPG on Pd loading can be attributed to lowering of crystallite size (9 nm) as well as the role of Pd particles in exhibiting spill-over mechanism on the SnO2 surface. Also selectivity of 3.0 wt% Pd:SnO2 toward LPG was confirmed by measuring its response to other reducing gases like acetone (CH3COCH3), ethanol (C2H5OH) and ammonia (NH3) at optimum operating temperature. (C) 2012 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: LPG sensor; Palladium; SnO2; Thick film

Studies on the resistive response of nickel and cerium doped SnO2 thick films to acetone vapor - Bagal, L. K.; Patil, J. Y.; Mulla, Imtiaz S.; Suryavanshi, S. S. (Ceramics International, 2012)
Undoped and Ni, Ce-doped nanocrystalline tin oxide were synthesized by co-precipitation route. Doped as well as undoped SnO2 compositions revealed single phase structure without any impurity. The lattice constant of SnO2 increases and the grain size decreases with doping of Ni and Ce. The responses of the sensing elements are evaluated by measuring the resistance change upon exposure to various test gases such as liquid petroleum gas (LPG), acetone, ethanol and ammonia. In comparison to LPG, ethanol, and ammonia the response towards acetone vapor increases markedly on simultaneous doping of Ni and Ce. For acetone vapors with 500 ppm at 300 degrees C, the undoped SnO2 shows 31% response, while with individual Ni or Ce doping it increases to 38 and 60%, respectively, however with simultaneous doping of Ni and Ce there is a significant enhancement up to 92%. The results of gas sensing measurements reveal that the thick films deposited on alumina substrates using screen printing technique give selectively a high response of (87%) with fast recovery (similar to 1 min) towards 100 ppm acetone at 300 degrees C. (c) 2012 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: (Ni plus Ce)-doping; Acetone vapor; Screen-printing; SnO2

Acetone vapour sensing characteristics of undoped and Zn, Ce doped SnO2 thick film gas sensor - Bagal, L. K.; Patil, J. Y.; Bagal, K. N.; Mulla, Imtiaz S.; Suryavanshi, S. S. (Materials Research Innovations, 2013)
The nanocrystalline materials of zinc and ceria doped tin oxide [(Zn+Ce)-SnO2] powders were synthesised by coprecipitation method and investigated for their sensing properties towards liquid petroleum gas (LPG), ethanol, ammonia and acetone vapour. The crystal structure and phase of the as synthesised and sintered powders were characterised by X-ray diffractometer and the microstructure by scanning electron microscopy. All the doped and undoped SnO2 compositions revealed single phase solid solution formation. Transmission electron microscope results indicated that well crystallised (Zn+Ce) doped SnO2 particles of size similar to 7 nm were obtained at the annealing temperature of 650 degrees C. The reduction in grain size of the metal oxide is a key factor to enhance the gas sensing properties. The doping of zinc, ceria in SnO2 has reduced the grain size and improved the gas response. The results of gas sensing measurements showed that the thick films deposited on alumina substrates using screen printing technique exhibited high response to acetone at an operating temperature of 300 degrees C. Further, the selectivity of the sensor towards acetone with respect to other reducing gases (LPG, ethanol and ammonia) was studied.
Keywords: Gas; Screen printing; Sensor; SnO2

Effect of Pd and Ce on the enhancement of ethanol vapor response of SnO2 thick films - Bagal, L. K.; Patil, J. Y.; Vaishampayan, M. V.; Mulla, Imtiaz S.; Suryavanshi, S. S. (Sensors and Actuators B-Chemical, 2015)
The undoped SnO2 and 4 wt% Ce-doped SnO2 were successfully synthesized by a facile co-precipitation route. The ternary systems were prepared by Pd-loading (0.5, 1.5 and 3.0 wt%) on the 4 wt% Ce-doped SnO2 nanoparticles. The structure and morphology of the nanocrystalline powders were investigated by X-ray diffraction, scanning electron microscopy and transmission electron microscopy techniques. The nanocrystalline powders were screen printed on the alumina substrates to form thick films to investigate their gas response properties. The gas response studies reveal that 4 wt% Ce-doped SnO2 with the loading of 3.0 wt% Pd exhibits high response (88%) towards ethanol (100 ppm) at an operating temperature of 250 degrees C with quick response (6 s) and rapid recovery (20 s). The high ethanol vapor response at lower operating temperature of this sensor is attributed to the spill-over mechanism of Pd particles present on the SnO2 surface and enhancement in alkalescence of SnO2 due to Ce-doping. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Ce-doped tin oxide; Gas sensor; Semiconductor; Thick film